Investigating the Potential of a Scenario Catalogue for Automated Driving Safety Evaluation to Cover Real-World Crashes - Marko Medojevic; Hisashi Imanaga; Jacobo Antona-Makoshi; Maki Kawakoshi; Hideaki Satoh (International Journal of Automotive Engineering, 2023)
Automated driving safety evaluation predominantly relies on scenario-based approaches. In this study, the authors adopt a functional scenario catalogue initially conceived by JAMA to evaluate automated driving safety on limited access highways. The potential of this catalogue to cover real-world crashes was investigated by comparing each scenario in the catalogue with crash patterns from two international data sources: the 2007 NHTSA’s pre-crash scenario typology for crash avoidance research report, and the 2020 IGLAD’s codebook. The results indicate the potential of the scenario catalogue to comprehensively cover both the NHTSA and the IGLAD crash scenario typologies.